Introduction to sociology - Giddens, Anthony (New York W.W. Norton & Company, 2021)
"The Introduction to Sociology, Twelfth Seagull Edition, features thoroughly revised coverage of the local and global impacts of increasing inequality. It offers new in-text and online tools to help students understand and apply theory to pressing social issues. A respected author team, up-to-date data, and new research examples ensure students get a thoughtful and current introduction to the discipline. And with a new full-color design-at the same low price-it is more engaging than ever"--
Includes bibliographical references and index.
Keywords: Sociology